Organizational Factors in the Performance Analysis of Healthy Indonesian Program Data Collection Employee with Family Approaches in Public Health Center - Kawidian Putri Bayu Alam; Septo Pawelas Arso; Nurhasmadiar Nandini (Jurnal Kesehatan Masyarakat (Undip), 2019)
Background: Data collection on the home visit in Semarang City must be completed in April 2019, but there were 17 public health centers have not reached 100% in June 2019. The public health center must developed strategies to improve employee performance to optimize data collection on the home visit by applying organizational factors. This study aims to analyzed organizational factors on the performance of PIS-PK employee in data collection on a home visit in Semarang City.Method: This was a qualitative research with a descriptive approach using the method of in-depth interview purposive sampling. This study was conducted in June-July 2019. The Coordinator and PIS-PK employee was the main informant. Triangulation informants in this research were regional cadres and head of the public health center, and the coordinator of PIS-PK in Semarang City. The analyzed factors were resources, supervision, leadership, organization structure, and work design.Results: The results of this research such as the resources provided in the data collection on home visits were completed. The supervision such as giving direction, guidance, monitoring and evaluating during the implementation was given well. The head of the public health center and the PIS-PK coordinator’s leadership in making decisions and solving problems showed well. The organizational structure and design of the work were poor, there was still an overlapping division of tasks so the performance did not optimal.Conclusions and Recommendation: Resources, supervision, leadership, organizational structure and work design are factors that support the employee performance. The performance of PIS-PK employee is not optimal because there were still overlapping divisions of tasks. It’s better if the public health center in Semarang City makes a division of job desk and the design of the implementation activities, so it can be more structured and monitored.Keywords: organizational factors, data collection on home visits, data collection employee.